Calidad de servicio y satisfacción del cliente en la empresa Paradise Green Club Iquitos, 2023 - Torres Mozombite, Rolly Alfonso (2023)
The main objective of the investigation was to know how the company Paradise Green Club, Iquitos 2023, related customer satisfaction with the quality of service. It is descriptive, uses a quantitative and correlational methodology, and uses a cross-sectional, non-experimental design. 50 customers of the Paradise Green Club business made up the population. The instrument was used for the compilation of information. Then, it was processed using a Microsoft Excel spreadsheet and IBM SPSS Statistics v26, yielding a Pearson correlation coefficient of 0.966, evidencing a strong correlation between the customer satisfaction criteria at Paradise Green Club, Iquitos 2023. As a result, it was The research ends by accepting the broad hypothesis and refuting the null hypothesis.